Luminescence Properties of Self-Aggregating TbIII-DOTA-Functionalized Calix[4]arenes - Mayer, Florian; Tiruvadi Krishnan, Sriram; Schühle, Daniel T.; Eliseeva, Svetlana V.; Petoud, Stéphane; Tóth, Éva; Djanashvili, Kristina (Frontiers in Chemistry, 2018)
Self-aggregating calix[4]arenes carrying four DOTA ligands on the upper rim for stable complexation of paramagnetic GdIII-ions have already been proposed as MRI probes. In this work, we investigate the luminescence properties of TbIII-DOTA-calix[4]arene-4OPr containing four propyl-groups and compare them with those of the analogue substituted with a phthalimide chromophore (TbIII-DOTA-calix[4]arene-3OPr-OPhth). We show that, given its four aromatic rings, the calix[4]arene core acts as an effective sensitizer of Tb-centered luminescence. Substituents on the lower rim can modulate the aggregation behavior, which in turn determines the luminescence properties of the compounds. In solid state, the quantum yield of the phthalimide derivative is almost three times as high as that of the propyl-functionalized analogue demonstrating a beneficial role of the chromophore on Тb-luminescence. In solution, however, the effect of the phthalimide group vanishes, which we attribute to the large distance between the chromophore and the lanthanide, situated on the opposite rims of the calix[4]arene. Both quantum yields and luminescence lifetimes show clear concentration dependence in solution, related to the strong impact of aggregation on the luminescence behaviour. We also evidence the variability in the values of the critical micelle concentration depending on the experimental technique. Such luminescent calix[4]arene platforms accommodating stable lanthanide complexes can be considered valuable building blocks for the design of dual MR/optical imaging probes.